Indigenous Peoples - The Inspection Panel (World Bank, Washington, DC, 2016)
The Inspection Panel was created in 1993 by the Board of Executive Directors of the World Bank to receive complaints submitted by people suffering harm allegedly caused by World Bank projects. This experience provides important lessons for both the Bank and for the global development community at large. The Panel therefore launched this series of publications to draw the main emerging lessons from its caseload. While Panel cases tend to highlight challenging projects where things went wrong and are not necessarily reflective of the Bank’s entire portfolio, the lessons nonetheless are important. This exercise is intended to help build the institutional knowledge base, enhance accountability, foster better results in project outcomes, and, ultimately, contribute to more effective development with shared prosperity for all. The series is organized around the most recurrent issues in Panel investigations. This report, the second in the series, covers Panel cases that focused on Indigenous Peoples’ issues. Currently, there are approximately 370 million self-identified Indigenous Peoples in some 90 countries worldwide. They are among the world’s most vulnerable, marginalized, and disadvantaged groups. According to the World Bank, while Indigenous Peoples own, occupy, or use a quarter of the world’s surface area, they safeguard 80 percent of its remaining biodiversity, and some of the most biologically important lands and waters are intact as a result of Indigenous Peoples’ stewardship. Their knowledge and expertise on how to adapt, mitigate, and reduce risks from climate change and natural disasters are considered vital. Adequately responding to these challenges requires considering Indigenous Peoples as fundamental stakeholders and important partners in the development process. The Bank has undertaken several reviews and evaluations of its Indigenous Peoples Policy since 1982.The Inspection Panel’s mandate covers projects financed by the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA). The Compliance Advisor Ombudsman handles complaints related to projects financed by the International Finance Corporation and the Multilateral Investment Guarantee Agency. In this report, the World Bank (or Bank) refers to IBRD and IDA only.